ANALISIS BILANGAN PECAHAN DALAM AL-QURAN DAN HADIST - Rahmayani, Rizki; Wahidah, Andina Nurul (IAIN Pontianak, 2023)
The purpose of this study is to discuss mathematics in fractional material contained in the Al-Qur'an and Hadith. This research is also expected to arouse the enthusiasm of students in learning fractions related to the Al-Qur'an and Hadith. This research method uses a qualitative approach to the study of literature (library research). The data collection technique used was a documentation study conducted by studying the Al-Qur'an and Hadith as well as other supporting scientific works. The results of this study identify fractional numbers contained in the Al-Quran and Hadith. The fractional numbers found in the Qur'an are 2/3, 1/2, 1/3, 1/4, 1/5, 1/6, 1/8 and 1/10. The eight fractional numbers are contained in, (1) QS. An-Nisa verse 14, (2) Q.S Al-Anfaal verse 41, (3) Q.S Saba' verse 45, and (4) Q.S Al-Muzammil verses 3, 4 and 20. Furthermore, the number of fractions contained in the Hadith is 1 /2, 1/3, 1/4, 1/5, 1/6, 1/7, 1/8, 1/9 and 1/10. The hadith about this fraction is contained in, (1) H.R Bukhari No 1079, (2) H.R. Abu Daud No. 1573, (3) H.R. Al Baihaqi No. 625, (4) H.R. Abu Dawud No 796, and (5) H.R. Muslim No. 557.